Flood insurance helps to make farmers in Bangladesh and India more resilient to climate shocks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
During 2020, IWMI worked with private-sector partners and NGOs to trial satellite-based weather insurance products to poor farmers in India and Bangladesh. As a result, more than 4,000smallholders received insurance payouts that helped them recover quickly from damaging floods. When the insurance was bundled with seeds and weather information, farmers’ resilience to climate shocks was further enhanced. IWMI is now working to scale up the use of satellite-based weather insurance in India and Bangladesh, and introduce it to new areas